The warehouse : a novel - Hart, Rob (Fiction writer) (Crown Publishers, 2019)
Zinnia never thought she'd be infiltrating Cloud. But now she's undercover, inside the walls, risking it all to ferret out the company's darkest secrets. And Paxton, with his ordinary little hopes and fears? He just might make the perfect pawn--if she can bear to sacrifice him.